1998
DOI: 10.1111/j.1600-0722.1998.tb02194.x
|View full text |Cite
|
Sign up to set email alerts
|

Enamel epithelium expresses bone sialoprotein (BSP)

Abstract: HF: Enamel epithelium expresses hone sialoprolein ( 8 P). Eur J Oral Sci /99 : 106 (suppll ): 33 1 336. \.. Eur J Oral ci. 199Bone sialoprotein ( B P) is a major non-collagenou extracellular matrix protein in bone and other mineralized connective ti ues. B P i synthesized and secreted by bone-. dentin-and cementum-forming cells. In this study we hypothesized that B P may be also involved in enamel formation through it postulated role in matrix mineralization. In situ hybridization with cR A probes for rat and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
3

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 5 publications
2
17
0
3
Order By: Relevance
“…1 G-L) in agreement with previous reports in vitro and in vivo (10,18). Expressional patterns of BSP protein analyzed by Western blot assay demonstrated that two bands were detected at positions, 39-and 27-kDa, respectively in the two mouse odontoblastic cells (Fig.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…1 G-L) in agreement with previous reports in vitro and in vivo (10,18). Expressional patterns of BSP protein analyzed by Western blot assay demonstrated that two bands were detected at positions, 39-and 27-kDa, respectively in the two mouse odontoblastic cells (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…High BSP expression is restricted to the mineralized connective tissues and seen at the onset of bone, dentin and cementum formation, indicating a role of this protein in the initial mineralization of these tissues (10,(18)(19). OPN is a secreted adhesive glycoprotein expressed in both mineralized and non-mineralized tissues (20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sialoproteins such as osteopontin (OPN), bone sialoprotein (BSP), and dentin sialoprotein (DSP) accumulate at the mineralization fronts in bone, dentin and other mineralizing tissues [1][2][3][4][5][6][7][8][9][10]. These proteins are part of an extended family of generally related secreted phosphoproteins, SIBLINGS (Small integrin-binding ligand, N-linked glycoproteinS), which share chromosomal location and general gene structure, but are not sequence related [11].…”
mentioning
confidence: 99%
“…Two dentin proteins, dentin sialoprotein (DSP) and dentin phosphoprotein (DPP), are tooth-specific. BSP, osteonectin, osteocalcin, and osteopontin are found in many types of odontogenic tumors, suggesting that these proteins play a role in pathological mineralization and/or tumor formation (114,(125)(126)(127). Expression of BMP, which induces bone and tooth formation, has been recognized in various types of odontogenic tumors (107)(108)128).…”
Section: Hard Tissue-related Proteinsmentioning
confidence: 99%